2008
DOI: 10.1158/1055-9965.epi-07-2761
|View full text |Cite
|
Sign up to set email alerts
|

Teeth Loss and Risk of Cancer at 14 Common Sites in Japanese

Abstract: Background: Tooth loss has been associated with a higher risk of several types of cancer. To clarify the significance of tooth loss to the risk of 14 common cancers, we conducted a large-scale, case-control study based on the Hospital-based Epidemiologic Research Program at Aichi Cancer Center. Methods: A total of 5,240 cancer subjects and 10,480 ageand sex-matched noncancer controls were recruited. Patients with 14 types of cancer newly diagnosed from 2000 to 2005 were eligible as case subjects, and new outpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
216
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(227 citation statements)
references
References 24 publications
7
216
1
3
Order By: Relevance
“…A case-control study conducted in Japan showed that a decreased number of remaining teeth was associated with the incidence of prostate cancer with a lower odds ratio (OR) of 0.49 (95%CI, 0.19-1.26) (Hiraki et al, 2008), while a similar finding was reported in follow-up investigation of the US male health professionals study . The multivariate HR value reported in that study was 0.7 (95%CI, 0.50-0.97) for subjects with 0-16 teeth vs. those with 25-32 teeth.…”
Section: Tooth Loss and Prostate Cancer Incidencementioning
confidence: 56%
See 4 more Smart Citations
“…A case-control study conducted in Japan showed that a decreased number of remaining teeth was associated with the incidence of prostate cancer with a lower odds ratio (OR) of 0.49 (95%CI, 0.19-1.26) (Hiraki et al, 2008), while a similar finding was reported in follow-up investigation of the US male health professionals study . The multivariate HR value reported in that study was 0.7 (95%CI, 0.50-0.97) for subjects with 0-16 teeth vs. those with 25-32 teeth.…”
Section: Tooth Loss and Prostate Cancer Incidencementioning
confidence: 56%
“…The case-control study was based on a Hospital-based Epidemiologic Research Program in Japan, and investigated associations between tooth loss and incidence rates of 14 common cancers. Although the risk for total cancer was not described, their findings showed that a greater number of missing teeth was associated with increased risks of head and neck, esophageal, and lung cancers, and decreased risk of prostate cancer (Hiraki et al, 2008). Also, for head and neck and esophageal cancers, stratified analyses by sex and age showed clear associations between tooth loss and cancer risk in women and younger subjects, but less clear associations in men and older subjects.…”
Section: Relationship Between Tooth Loss and Cancer Mortality 41 Toomentioning
confidence: 98%
See 3 more Smart Citations